Pengaruh Struktur Kepemilikan Manajerial, Kepemilikan Institusional dan Profitabilitas terhadap Kebijakan Dividen dalam Mengontrol Konflik Keagenan - Masdupi, Erni -; Ningsih, Risma - (Jurnal Kajian Manajemen Bisnis, 2015)
The purpose of this study is to analyze the effect of managerial ownership, institusional ownership, and profitability on the dividend policy. The research populations are 481 listed companies on the Indonesia Stock Exchange (IDX) in the period 2009-2003. 235 companies-years observations were selected with technical sampling was purposive. The results showed that managerial ownership, institusional ownership do not have significant effect on the dividend policy and profitability which proxied by return on equity significantly and negatively affected the dividend policy of listed companies on IDX.